METHODICAL WORK IN THE PROFESSIONAL SYSTEM TEACHER TRAINING - Dudnichenko, N.V. (Pedagogy of Higher and Secondary Education, 2001)
The article deals with the main forms of methodic work of school which help to develop creative style of teachers’ activity.